A multi‐center experience of ablation index for evaluating lesion delivery in typical atrial flutter. Issue 6 (4th May 2021) - Maclean, Edd; Simon, Ron; Ang, Richard; Dhillon, Gurpreet; Ahsan, Syed; Khan, Fakhar; Earley, Mark; Lambiase, Pier D.; Rosengarten, James; Chow, Anthony W.; Dhinoja, Mehul; Providencia, Rui; et al.
Abstract: Background: Anatomical studies demonstrate significant variation in cavotricuspid isthmus (CTI) architecture. Methods: Thirty‐eight patients underwent CTI ablation at two tertiary centers. Operators delivered 682 lesions with a target ablation index (AI) of 600 Wgs. Ablation parameters were recorded every 10–20 ms. Post hoc, Visitags were trisected according to CTI position: inferior vena cava (IVC), middle (Mid), or ventricular (V) lesions. Results: There were no complications. 92.1% of patients (n = 35) remained in sinus rhythm after 14.6 ± 3.4 months. For the whole CTI, peak AI correlated with mean impedance drop (ID) (R 2  = 0.89, p  < .0001). However, analysis by anatomical site demonstrated a non‐linear relationship Mid CTI (R 2  = 0.15, p  = .21). Accordingly, while mean AI was highest Mid CTI (IVC: 473.1 ± 122.1 Wgs, Mid: 539.6 ± 103.5 Wgs, V: 486.2 ± 111.8 Wgs, ANOVA p  < .0001), mean ID was lower (IVC: 10.7 ± 7.5Ω, Mid: 9.0 ± 6.5Ω, V: 10.9 ± 7.3Ω, p  = .011), and rate of ID was slower (IVC: 0.37 ± 0.05 Ω/s, Mid: 0.18 ± 0.08 Ω/s, V: 0.29 ± 0.06 Ω/s, p  < .0001). Mean contact force was similar at all sites; however, temporal fluctuations in contact force (IVC: 19.3 ± 12.0 mg/s, Mid: 188.8 ± 92.1 mg/s, V: 102.8 ± 32.3 mg/s, p  < .0001) and catheter angle (IVC: 0.42°/s, Mid: 3.4°/s, V: 0.28°/s, p  < .0001) were greatest Mid CTI. Use of a long sheath attenuated these fluctuations and improved energy delivery. Conclusions: Ablation characteristics vary across the CTI. At the Mid CTI, higher AI values do not necessarily deliver more effective ablation; this may reflect localized fluctuations in catheter angle and contact force.